Transaction costs, risk preference and market participation: Field experiments with value chain actors in Ethiopia and Eritrea - Kassie, Girma T.; Abate, Gashaw T.; Alene, Arega; Najjar, Dina (2019)
The International Center for Agricultural Research, International Food Policy Research Institute, International Institute of Tropical Agriculture, Gondar Agricultural Research Center in Ethiopia, and National Agricultural Research Institute of Eritrea are implementing a research project in Ethiopia and Eritrea. The research project is entitled “Transaction Costs, Risk Preference and Market Participation - Field Experiments with Value Chain Actors in Ethiopia and Eritrea.”